Physiological responses of athletes to rhythmic loads - Kalinnikova, Y. G.; Inozemtseva, E. S.; Kapilevich, L. V. (Theory and Practice of Physical Culture, 2017)
Objective of the study was to rate effects of variable rhythmic loads on the athlete's functional status. The physiological and psycho-physiological responses to physical loads in the female athletes engaged in aerobics were proved to be largely dependent on the rhythm and pace of the musical illustration, with the latter found to contribute to the coherence of the electrical activity in the cerebral cortex. On the other hand, physical loads to music of inappropriate rhythm and tempo were found to suppress the coherence. Forecast algorithms for the psycho-physiological responses under variable physical loads need to be developed with due consideration for the primary body functional state; and the algorithms could be beneficial for the training process efficiency improvement via better mobilisation of the bodily resources; higher resistance to physical and mental loads; and faster adaptation to variable external environments. Fitness aerobics may facilitate the trainees` progress conditional on the following: prudent design of the training sessions with their elements focused on different functionality aspects; perfect execution techniques with due load management; and encouraging music with appropriate rhythm and tempo.